2013
DOI: 10.3109/13880209.2013.799706
|View full text |Cite
|
Sign up to set email alerts
|

Toxic rather than neuropharmacological effect ofTernstroemia sylvaticafruits and identification of 28-O-[β-l-6-rhamnopyranosyl]-R1-barrigenol as a new compound with toxic effects in mice

Abstract: Results: Crude extracts of T. sylvatica fruits, separated from seed and pericarp, showed sedative effect in mice. The aqueous (ED 50 ¼ 4.9 AE 0.8 mg/kg) seed extracts is the most active among them. This extract also decrease locomotor activity and disrupt motor coordination of mice. This extract was also the most toxic extract (LD 50 ¼ 5.0 AE 1.4 mg/kg; i.p.). The triterpene glycoside 28-O-[b-L-6-rhamnopyranosyl]-R 1 -barrigenol was identified in this extract as one of the active sedative compounds (ED 50 ¼ 0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 21 publications
(27 reference statements)
0
7
0
Order By: Relevance
“…The neuropharmacological profile was performed by the intraperitoneal administration of the DMR of each compounds 30 min before the test: the sedative activity was evaluated in the exploratory cylinder test [9] , the motor coordination on rota-rod test (Rota-rod Treadmills for mice, constant speed model 7600, Ugo Basile; 4 cm diameter,16 rpm), the myo-relaxant effect in the traction test [14] , the anxiogenic effect in the hole board test (Hole Board Apparatus, Ugo Basile 6650) [14], and the locomotor activity in the open field test (IR Actimeter LE8811, Panlab/Harvard Apparatus, MA, USA) [14] using conventional protocols. Diazepam (2.5 mg/kg) was used as reference drug in these tests.…”
Section: Neuropharmacological Profilementioning
confidence: 99%
“…The neuropharmacological profile was performed by the intraperitoneal administration of the DMR of each compounds 30 min before the test: the sedative activity was evaluated in the exploratory cylinder test [9] , the motor coordination on rota-rod test (Rota-rod Treadmills for mice, constant speed model 7600, Ugo Basile; 4 cm diameter,16 rpm), the myo-relaxant effect in the traction test [14] , the anxiogenic effect in the hole board test (Hole Board Apparatus, Ugo Basile 6650) [14], and the locomotor activity in the open field test (IR Actimeter LE8811, Panlab/Harvard Apparatus, MA, USA) [14] using conventional protocols. Diazepam (2.5 mg/kg) was used as reference drug in these tests.…”
Section: Neuropharmacological Profilementioning
confidence: 99%
“…32 Several plants that have traditionally been used to relieve anxiety, sleep disorders, and seizures have not necessarily been evaluated to demonstrate nontoxicity attributed to their consumption. 33 Although medicinal plants, or their combinations, have a multimodal and synergistic mechanisms of action, their potential use for the development of drugs brings possible associated drawbacks. There are few studies showing bioequivalence between chemical entities obtained from natural products or botanical extracts rich in bioactive compounds, which prevents them from being proposed as viable conventional drugs.…”
Section: Food or Medicinal Plants With Anxiolytic And Antidepressant ...mentioning
confidence: 99%
“…This folk medicinal plant from the family Theaceae is distributed in Ciudad de México, Hidalgo, San Luis Potosi, Chiapas, Querétaro, Veracruz Tamaulipas and Sinaloa [ 47 , 98 , 99 ]. Pharmacological studies of T. sylvatica fruits have demonstrated that the common anxiolytic uses of this plant are due to its sedative properties [ 100 , 101 ]. In addition, its traditional uses are supported by its other actions, such as anti-inflammatory and analgesic effects displayed in a murine model, suggesting that its actions are mediated by the activation of antioxidant mechanisms [ 99 ].…”
Section: Preclinical Studies Of Mexican Medicinal Plants Used In Inflammatory and Neuropathic Pain Treatmentmentioning
confidence: 99%
“…In addition, its traditional uses are supported by its other actions, such as anti-inflammatory and analgesic effects displayed in a murine model, suggesting that its actions are mediated by the activation of antioxidant mechanisms [ 99 ]. Furthermore, Balderas-López et al [ 100 ] demonstrated that triterpene glycoside 28- O -[β- l -6-rhamnopyranosyl]-R 1 -barrigenol isolated from aqueous extracts of seeds of T. sylvariva fruits is the bioactive compound responsible for its sedative effects, but this also presents toxic and lethal effects.…”
Section: Preclinical Studies Of Mexican Medicinal Plants Used In Inflammatory and Neuropathic Pain Treatmentmentioning
confidence: 99%